Evidence of steep declines in the heavily traded Javan White-eye Zosterops flavus from repeated standardised surveys. (29th June 2023) - van Balen, S. (Bas); Saryanthi, Ria; Marsden, Stuart
Summary: Many Indonesian, and in particular Javan, birds are suspected to have declined dramatically as a result of unsustainable trapping for the cagebird trade, but quantitative evidence of the scale of declines is lacking for the great majority of species. We conducted field surveys of the heavily traded Javan White-eye Zosterops flavus at 19 key sites in 2018–2019 matching the methods and personnel used in baseline surveys done around 10 years earlier. Overall numbers counted were 84% lower in the later survey, and while more white-eyes were recorded at three sites in 2018–2019, there was a significant decline in numbers across all sites. The three sites with highest numbers in 2006–2019 (502 birds counted) had 22 individuals counted in 2018–2019, but there was no overall trend for 'declines' to be greater at sites that held more birds originally. Declines in white-eyes were much steeper than those of several lesser-traded bird species at the sites, suggesting that trapping has been a more important driver of declines than habitat changes such as conversion of mangrove to shrimp ponds. Small numbers of white-eyes were recorded at several previously unvisited sites, but we suggest that the species, on Java at least, has shown declines in the region of 80% over the last 10 years. Although since 2018 Javan White-eye is legally protected, we urge that this protection is extended to all white-eye species, because of their similarity.